RANCANG BANGUN PROTOTYPE ALAT PENGERING CENGKEH BERBASIS MIKROKONTROLER DAN SENSOR DHT 11 - Lisa Fitriani Ishak (Yayasan Nusantara Hasana Berdikari, 2025)
Cloves are one of the leading commodities in Indonesia. This is quite reasonable because Indonesia is an agricultural country. However, cloves have an obstacle, namely they are easily rotten if they are still fresh or have not undergone a drying process. At this time, the drying that is done is natural drying, namely using direct sunlight. In connection with the uncertainty of the drying process during the rainy season, I want to provide innovation by designing a clove dryer based on a microcontroller and DHT11 sensor. The design of this tool uses an Uno microcontroller, relay, and DHT11 sensor as a temperature sensor that is programmed as an output so that the tool can read the drying temperature. The heating element will activate and turn off when the temperature is excessive and the fan also functions as a heat sink. For monitoring, a 16x2 LCD is used as a display of temperature and humidity. In making this tool, the temperature in the drying box is controlled at a temperature of 50-60⁰C, which will allow the drying process with the dried sample being cloves that have an initial water content of ±80% to a dryness level of ±8%.